Contact resistivity reduction on lowly-doped n-type Si using a low workfunction metal and a thin TiOX interfacial layer for doping-free Si solar cells. (September 2017) - Cho, Jinyoun; Debucquoy, Maarten; Recaman Payo, Maria; Malik, Shuja; Filipič, Miha; Radhakrishnan, Hariharsudan Sivaramakrishnan; Bearda, Twan; Gordon, Ivan; Szlufcik, Jozef; Poortmans, Jef
Abstract: Eliminating a doping process could be an effective way to reduce the production cost of c-Si cells. However, in absence of highly doped Si, the formation of a high quality contact is not straightforward. The lack of field-effect passivation from a lowly doped region can lead to a high recombination current density at the contacts (J0, metal ) and moreover, contact resistivity (ρC ) typically increases when doping level is decreasing. In this work we focus on reducing the contact resistivity of an electron-selective contact for doping-free cells. Although the effect of low work function metals (LWMs) in combination with an i-a-Si:H layer has already been reported, the synergy effect of a LWM and a MIS (Metal-Insulator-Semiconductor) contact structure on top of the i-a-Si:H has not been reported yet. Here, we demonstrate a new ATOM (i-a-Si:H / TiOX / low workfunction metal) contact structure as an electron-selective contact using an i-a-Si:H layer, a TiOX interfacial layer and Ca (Φ = 2.9eV) without requiring an additional n + doping process. The addition of TiOX in between the i-a-Si:H layer and the Ca decreases the ρC by about 2 orders of magnitude. Despite of increased J0, metal due to e-beam processing of TiOX, the Ca based ATOM contact increases the potential max efficiency up to 25 %. To the best of our knowledge, this is the first demonstration of an electron-selective contact comprising a low work function metal, an interfacial TiOX and an i-a-Si:H passivation layer. This type of contact could be a promising route for the optimization of doping-free cells